Graded Cerebellar Lobular Volume Deficits in Adolescents and Young Adults with Fetal Alcohol Spectrum Disorders (FASD). (14th April 2020) - Sullivan, Edith V; Moore, Eileen M; Lane, Barton; Pohl, Kilian M; Riley, Edward P; Pfefferbaum, Adolf
Abstract: The extensive prenatal developmental growth period of the cerebellum renders it vulnerable to unhealthy environmental agents, especially alcohol. Fetal alcohol spectrum disorders (FASD) is marked by neurodysmorphology including cerebral and cerebellar volume deficits, but the cerebellar lobular deficit profile has not been delineated. Legacy MRI data of 115 affected and 59 unaffected adolescents and young adults were analyzed for lobular gray matter volume and revealed graded deficits supporting a spectrum of severity. Graded deficits were salient in intracranial volume (ICV), where the fetal alcohol syndrome (FAS) group was smaller than the fetal alcohol effects (FAE) group, which was smaller than the controls. Adjusting for ICV, volume deficits were present in VIIB and VIIIA of the FAE group and were more widespread in FAS and included lobules I, II, IV, V, VI, Crus II, VIIB, and VIIIA. Graded deficits (FAS < FAE) were consistently present in lobules VI; neither group showed volume deficits in Crus I or IX. Neuroradiological readings blind to diagnosis identified 20 anomalies, 8 involving the cerebellum, 5 of which were in the FAS group. We speculate that the regional cerebellar FASD-related volume deficits may contribute to diagnostically characteristic functional impairment involving emotional control, visuomotor coordination, and postural stability.